Impact of Different Therapeutic Protocols on Blood Biochemical Markers and Fertility in Anestrus Sahiwal Cows - Husain, Safayat; Kumar, Rajesh; Singh, Bhoopendra; Srivastava, Sushant; Kumar, Rabindra; Kumar, Pramod; Haque, Nilufar (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Bovine anestrus syndrome is a multifactorial disorder of the reproductive system. The problem is severe in suburban and rural areas of the country. The present study was aimed to evaluate the effect of different therapy on biochemical parameters and fertility response in 24 anestrus Sahiwal cows. Anestrus cows were randomly divided into four equal groups of six animals each, and were subjected with Lugol’s iodine 2%, cervical painting with per rectal massage of genitalia thrice on alternate day (G1, n=6), XXX herbal bolus 1 bid for 2 days, repeated on day 11 & 12 later in non-respondents (G2, n=6), and modified ovsynch protocol which consisted of 100 mg hydroxy progesterone caproate injected daily s/c for 6 days followed by inj. GPG (G3, n=6), while one group was kept as untreated control (G4, n=6). Blood samples were collected thrice from all cows, i.e., pretreatment day-0 (S1); post-treatment at induced estrus/AI (S2) and day 21 post-AI (S3), for estimation of serum progesterone and biochemical constituents. In general, except progesterone, the mean values of serum glucose, total cholesterol, total protein, albumin, calcium and phosphorus were significantly (p<0.05) lower at d-0 than the corresponding values at induced estrus and day 21 post-AI in treatment groups G1, G2 and G3; whereas, the periodic values did not differ significantly in control group G4. The estrus induction response was 100% in all treated cows with comparable conception rates among different therapeutic protocols (83.33, 66.66 & 83.33 %) as against nil response in control group G4. The results suggest that bovine anestrus syndrome can be managed well with comparatively low-cost Lugol’s iodine and herbal therapeutics.